2009
DOI: 10.1007/s10548-009-0103-8
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Connections Between Dorsal and Ventral Visual Streams in Humans: Evidence by TMS/EEG Co-Registration

Abstract: Parietal cortex subserves various cognitive tasks, ranging from attention to visuo-motor skills. It is part of a parieto-frontal network involved in attention, and part of the visual dorsal stream, opposed to the visual ventral stream, although increasing evidence suggests interchange of information between them. In this study, co-registration of Transcranial Magnetic Stimulation (TMS) and Electroencephalographic activity (EEG) has been used to investigate the spreading of cortical connections from the parieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 71 publications
(115 reference statements)
6
43
0
Order By: Relevance
“…Integrated information from the dorsal and ventral streams may be fed back from the prefrontal cortex in order to modulate processing within the two networks according to task demands. In support of this, a recent study observed that TMS stimulation of the left parietal cortex resulted in activation of prefrontal regions beginning approximately 100 ms after stimulus onset, followed by subsequent activation of fusiform and middle temporal regions at a later time period, approximately 170 ms after stimulation (Zanon et al, 2010). Although this does not negate the existence of a direct influence of dorsal parietal regions on ventral stream processing within the temporal lobe, the time course of these effects is highly suggestive that this dorsalventral feedback loop may be mediated via the prefrontal cortex.…”
Section: The 'Feedback' Accountmentioning
confidence: 74%
See 1 more Smart Citation
“…Integrated information from the dorsal and ventral streams may be fed back from the prefrontal cortex in order to modulate processing within the two networks according to task demands. In support of this, a recent study observed that TMS stimulation of the left parietal cortex resulted in activation of prefrontal regions beginning approximately 100 ms after stimulus onset, followed by subsequent activation of fusiform and middle temporal regions at a later time period, approximately 170 ms after stimulation (Zanon et al, 2010). Although this does not negate the existence of a direct influence of dorsal parietal regions on ventral stream processing within the temporal lobe, the time course of these effects is highly suggestive that this dorsalventral feedback loop may be mediated via the prefrontal cortex.…”
Section: The 'Feedback' Accountmentioning
confidence: 74%
“…Electrophysiological (EEG and MEG) studies with both humans and non-human primates have provided evidence regarding the time windows in which regions along the dorsal and ventral pathways are activated, and have revealed some interesting patterns of activation and temporal dissociations which may shed some light on if and when dorsal and ventral information may interact during the course of their processing (Ahveninen et al, 2006;Alain, Arnott, Hevenor, Graham, & Grady, 2001;Alain et al, 2009;Anourova et al, 2001Anourova et al, , 2003Brunetti et al, 2005;Ellison & Cowey, 2007;Laycock, Crewther, Fitzgerald, & Crewther, 2009;Leavitt, Molholm, Gomez-Ramirez, & Foxe, 2011;Lewald & Getzmann, 2011;Rosazza et al, 2009;Wang, Wu, & Li, 2008;Zanon, Busan, Monti, Pizzolato, & Battaglini, 2010).…”
Section: When Could Dorsal-ventral Interaction Take Place?mentioning
confidence: 99%
“…In this example, areas in the occipital cortex were targeted using a nose reference and an Fz ground 7 . For other examples see 3,4,27,29,30 . Note that data can be re-referenced offline to a new reference as needed, such as the common average.…”
Section: Setting Up the Eeg And The Neuronavigation System And Condumentioning
confidence: 99%
“…Literature is summarized along these classifications, and it is argued that TMS-EEG is crucial to better understanding the neuronal underpinning of the disruptive and beneficial behavioral effects of TMS as well as null results; the latter potentially carried by compensational reorganization after TMSinterference. One example of the inductive approach is provided in Zanon et al (2009), studying the connectivity of the parietal cortex with TMS-EEG. Alex Rotenberg (2009) then focuses on plausible TMS-EEG applications in epilepsy and similarly reviews findings along three classes: (i) A ''diagnostic'' use of EEG-responses to TMS in order to measure potential TMS-provoked spikes for seizure focus localization; (ii) a ''therapeutic'' use of TEP-amplitude as a measure of individual cortical excitability to guide rTMS-treatment for seizure reduction (see also Brodbeck et al 2009 on rTMS-induced changes in individual spike patterns as a measure of individual treatment susceptibility), or (iii) a ''real-time interactive'' use to abort seizures by TMS-timing in dependence on underlying EEG patterns (as shown to be effective in animals).…”
Section: In This Special Issuementioning
confidence: 99%